2009
DOI: 10.1111/j.1469-0691.2009.02883.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal structure and 21-year evolution of Streptococcus pneumoniae serotype 1 isolates in northern Spain

Abstract: This study of 135 serotype 1 pneumococcal isolates (88 invasive and 47 non-invasive), collected between 1987 and 2007, gave eight sequence types (217, 227, 228, 304, 305, 306, 3860 and 3861) that group, using eBurst, into three different lineages and one singleton. The annual incidence of serotype 1 invasive episodes per million inhabitants increased from 1.8 in 1987-1993 to 4.0 in 1994-2000, and to 25.6 in 2001-2007. ST228 was the predominant clone until 1998. ST306 first appeared in 1998 and became the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In Portugal serotype 1 was the second most important serotype in adult IPD between 2006–2008 [6]. In neighboring Spain, outside the Madrid area where PCV7 was available but not included in the national immunization plan similar to Portugal, an increased importance of serotype 1 in IPD both in the group targeted for PCV7 vaccination as well as in older children and adults was also documented [39]. The decline in the importance of serotype 1 as a cause of IPD with age in adults reported previously [6] was also seen in this period.…”
Section: Discussionmentioning
confidence: 92%
“…In Portugal serotype 1 was the second most important serotype in adult IPD between 2006–2008 [6]. In neighboring Spain, outside the Madrid area where PCV7 was available but not included in the national immunization plan similar to Portugal, an increased importance of serotype 1 in IPD both in the group targeted for PCV7 vaccination as well as in older children and adults was also documented [39]. The decline in the importance of serotype 1 as a cause of IPD with age in adults reported previously [6] was also seen in this period.…”
Section: Discussionmentioning
confidence: 92%
“…The MLST306 serotype 1 clone has emerged as being responsible for over 80% of serotype 1 diseases in many parts of the world, and has been associated with invasive pneumococcal disease outbreaks [9,10,12,13]. MLST306 pneumococci express allele 5 PLY which differs in a few amino acids from haemolytic allele 1 PLY and lacks any haemolytic activity but retains the ability to bind to cholesterol-containing membranes [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, dominating clones of serotypes 1 and 8 are frequently found in invasive diseases that, however, show lower case-fatality rates [4][5][6][7]. Among serotype 1 pneumococci, the recently emerging MLST306 clone now dominates by over 80% in many parts of the world [8][9][10][11][12][13]. While the degree of encapsulation positively associates with colonization prevalence and virulence [5], other bacterial factors that affect the interaction with the host´s innate immune system might also play a role.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent serotype in patients identified by culture is serotype 1, as in other regions of Spain and in Portugal. Marimon et al [19] reported an increase in the number of IPD cases in children caused by serotype 1 in the Basque region of Spain following the introduction of PCV7. Nunes et al [20] reported an emergence of serotype 1 lineage of pneumococci among healthy carriers in Portugal after 2003.…”
Section: Discussionmentioning
confidence: 99%